Particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material and preparation method thereof
By optimizing the composition of copper alloy and deformation heat treatment process, a high-strength, high-conducting copper-based composite material with enhanced particle whisker mixing was prepared, which solved the problem of coating melting and sticking caused by the low-melting alloy reaction of the electrode material, achieved excellent mechanical properties and anti-melting properties, extended the electrode life and reduced the cost of use.
Patent Information
- Application Number
- CN202411925291.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-15
AI Technical Summary
During long-term use, existing electrode materials are prone to melt and stick to the electrode due to low melting point alloy reaction, resulting in a decrease in welding quality and shortening of electrode life, and the inability to achieve continuous mass production, which increases the cost of use.
By optimizing the composition of the copper alloy and combining with the deformation heat treatment process, a high volume fraction intermetallic hard phase is generated in situ to prepare a high-strength, high-conducting copper-based composite material with enhanced particle whisker mixing. The material improves the hardness, tensile strength and conductivity of the alloy through the hybrid enhancement of M16X6Si7 particles and MXSi whiskers.
It achieves excellent mechanical properties and anti-melt properties of electrode materials, extends the service cycle of the electrode, reduces the cost of use, and is suitable for industrial large-scale production.
Smart Images

Figure CN119824273A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of copper-based composite material preparation, and in particular to a particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material and a preparation method thereof. Background Art
[0002] Copper alloys are widely used in the fields of resistance welding electrodes and electrical contacts due to their outstanding electrical conductivity. However, during the long-term service of electrodes or contacts, the arc generated by welding or contact breaking will inevitably cause wear, deformation and ablation of the electrodes or contacts. In particular, when the component contains low-melting-point alloy components, such as zinc-based coatings on steel plates, aluminum alloys, etc., the low-melting-point materials contact and react with the electrodes, and the coating melts and sticks to the electrodes, resulting in a sharp decline in welding quality and welding efficiency, shortened electrode life, and the need to frequently interrupt welding to replace and grind the electrodes. In addition, since the resistance welding process has restrictions on the size and shape of the electrode head, and has high processing requirements for the electrode contact surface, continuous batch production is not possible, which further increases the cost of using the electrode.
[0003] At present, researchers at home and abroad mostly use the following methods to reduce the adhesion of electrode materials or the fusion welding of contacts: 1. Reduce the contact resistance between the electrode head and the welding plate or contact by introducing trace additives to reduce the temperature rise; 2. Coat the surface of the electrode head or contact with ceramic particles by chemical plating or spraying to reduce the diffusion between the electrode head and the welding plate; 3. Optimize the welding process, reduce the contact resistance, and inhibit the occurrence of adhesion. Although the above methods can effectively inhibit the occurrence of electrode adhesion or contact fusion welding, the regeneration of the material is poor, which affects the long-term use of the electrode.
[0004] In recent years, it has become an important copper alloy design and preparation concept to introduce reinforcements of different particle sizes, different morphologies, different properties or different dimensions into the matrix to form a hybrid system, and to use the hybrid enhancement effect to prepare materials with better comprehensive performance. For low-melting point welding materials, ceramics can effectively inhibit the diffusion between the welding plate material and the electrode, and improve the life of the component. Therefore, based on the design concept of hybrid enhancement, a specific process is used to in-situ generate a high volume fraction of intermetallic compound hard phases on the copper alloy matrix. On the basis of ensuring anti-melting and regeneration properties, developing an electrode or contact material with excellent mechanical properties and a long service life is the current key research direction in this field. The present invention contributes new ideas to the research and development of copper alloys, and provides more powerful support for the development of resistance welding and contact industries. Summary of the invention
[0005] In view of the shortcomings of the prior art, the present invention provides a method for preparing a particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material. The method optimizes and adjusts the alloy composition and combines the deformation heat treatment process to obtain a particle whisker hybrid reinforced electrode material, thereby achieving the purpose of having both excellent mechanical properties and anti-melting adhesion.
[0006] The particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material and the preparation method thereof of the present invention include the following elements in percentage by mass: M 1.5-10.0%, Si 0.3-3.0%, X 0.3-2.5%, and the rest are Cu and unavoidable impurities;
[0007] The M is at least one of Ni and Co; the X is one or more of Ti, Zr, Mn, V, Nb, and Cr.
[0008] The M element can be dissolved in the Cu matrix and form a relatively uniform solid solution. After solution treatment and aging heat treatment, the M element can form a dispersed nano-reinforced phase M2Si with the Si element, wherein M2Si is one of Ni2Si, Co2Si, and (Ni,Co)2Si, thereby improving the hardness and strength of the alloy.
[0009] The X element is a very effective grain refining element in Cu alloys. A trace amount of the X element can have a significant grain refining effect on the alloy.
[0010] Preferably, the composite material contains uniformly distributed M 16 X6Si7 particles and MXSi whiskers;
[0011] The M 16 The volume fraction of X6Si7 particles in the whole alloy is 1.0-8.0%, and the diameter is 1-10 μm;
[0012] The volume fraction of the MXSi whisker in the whole alloy is 0-4.0%, the radial dimension is 50-300nm, the aspect ratio is 50-300, and the alloy skeleton is formed in a network shape.
[0013] The M, Si and X elements in the alloy of the present invention are important elements for forming the G phase. During the smelting process, two micron-sized strengthening phases with different morphologies and sizes can be formed in the Cu matrix, namely, M 16 X6Si7 (G phase) particles and MXSi whiskers. 16 The Ni and Co elements represented by the M element in the X6Si7 particles and MXSi whiskers can be replaced with each other, and the Ti, Zr and other elements represented by the X element can also be replaced with each other. The MXSi whiskers form a mesh-like alloy skeleton, which further strengthens the alloy strength and heat resistance, and effectively improves the alloy's anti-melting and sticking properties.
[0014] The preparation method of the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material comprises the following steps:
[0015] (1) Melting: weigh the raw materials according to the ratio, first place the electrolytic pure copper in a crucible, evacuate the vacuum medium frequency induction furnace, fill it with argon protection, and then heat and melt it. After the copper is completely melted, add M metal, crystalline silicon and X metal in sequence. After all are melted, keep the temperature for 5 to 10 minutes and then vacuum cast. After cooling for 20 to 30 minutes, take it out of the furnace to obtain an ingot;
[0016] (2) Temperature-controlled hot rolling: After removing the oxide layer on the surface of the ingot by turning, the ingot is kept at a temperature of 850-1000°C for 2-6 hours, and then hot rolled to obtain a plate;
[0017] (3) Solution quenching: The hot-rolled plate is kept at 900-1000°C for 1-4 hours, followed by water quenching;
[0018] (4) Cold rolling deformation: the plate after solution treatment is cold rolled to obtain a cold rolled plate;
[0019] (5) Aging heat treatment: The cold-rolled sheet is subjected to aging heat treatment, and then air-cooled to obtain the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material.
[0020] Preferably, the M metal in step (1) is at least one of a nickel block and a cobalt block.
[0021] Preferably, the X metal in step (1) is one or more of titanium sponge and Cu-X alloy, and the X is one or more of Zr, Mn, V, Nb and Cr.
[0022] Preferably, the smelting temperature in step (1) is 1280-1360°C.
[0023] Preferably, the initial rolling temperature of the hot rolling in step (2) is 850-1000° C., the final rolling temperature is ≥650° C., and the total hot rolling processing rate is 50-95%.
[0024] Preferably, the total processing rate of the cold rolling in step (4) is 20 to 90%.
[0025] Preferably, the temperature of the aging heat treatment in step (5) is 375-525° C., and the holding time is 0.5-24 h.
[0026] The present invention provides a particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material and a preparation method thereof. Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The process is simple and stable, with high efficiency and low preparation cost;
[0028] 2. M in alloy 16 X6Si7 particles and MXSi whiskers are precipitated in situ, and have high-quality interface bonding with the metal matrix;
[0029] 3. The alloy structure is uniform and stable, with good machinability, controllable content of particles and whiskers, and enhanced synergy, which is suitable for industrial large-scale production;
[0030] 4. The prepared copper-based composite material has excellent comprehensive properties after heat treatment, including hardness of 120-300 HV, tensile strength of 300-900 MPa, conductivity of 20-80% IACS, and high temperature softening resistance of more than 500°C. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a scanning electron microscope image of the as-cast microstructure of the particle whisker hybrid reinforced Cu-Ni-Si-Ti composite material prepared in Example 1;
[0032] Figure 2 This is a scanning electron microscope image of the as-cast microstructure of the particle whisker hybrid reinforced Cu-Co-Si-Ti electrical composite material prepared in Example 2;
[0033] Figure 3 This is a scanning electron microscope image of the as-cast microstructure of the particle whisker hybrid reinforced Cu-Ni-Si-Ti composite material prepared in Comparative Example 1;
[0034] Figure 4 This is a scanning electron microscope image of the deep corrosion microstructure of the particle whisker hybrid reinforced Cu-Ni-Si-Ti composite material prepared in Comparative Example 1;
[0035] Figure 5 This is a scanning electron microscope image of the as-cast microstructure of the particle whisker hybrid reinforced Cu-Co-Ni-Si-Zr composite material prepared in Comparative Example 2. DETAILED DESCRIPTION
[0036] The present invention will be further described below in conjunction with the embodiments.
[0037] Example 1
[0038] A particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material is composed of the following raw materials in percentage by mass: 93.95% of electrolytic pure copper, 4.00% of nickel block, 0.83% of pure silicon wafer and 1.22% of sponge titanium.
[0039] The preparation method of the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material comprises the following steps:
[0040] (1) Placing electrolytic pure copper at the bottom of a crucible, evacuating the vacuum medium frequency induction furnace, filling it with argon gas for protection, and then heating it at a melting temperature of 1300° C. After the copper is completely melted, a nickel block, a pure silicon wafer, and a titanium sponge are added in sequence. After all of them are melted, the mixture is kept warm for 5 minutes and then vacuum cast. After cooling for 20 minutes, the vacuum is released and the furnace is taken out to obtain a Cu-Ni-Si-Ti ingot;
[0041] (2) temperature-controlled hot rolling: after removing the surface oxide layer of the Cu-Ni-Si-Ti ingot by turning, the ingot is kept at a temperature of 1000°C for 4 hours and then hot rolled. The initial rolling temperature of the hot rolling is 1000°C, the final rolling temperature is 650°C, and the total hot rolling processing rate is 80%;
[0042] (3) Solution quenching: The hot-rolled Cu-Ni-Si-Ti composite material was kept at 1000 °C for 4 h and then water-quenched;
[0043] (4) Cold rolling deformation: the Cu-Ni-Si-Ti composite material plate after solid solution treatment is cold rolled, and the total cold rolling processing rate is 60%;
[0044] (5) Aging heat treatment: The cold-rolled Cu-Ni-Si-Ti composite sheet was kept at 450°C for 4 h and then air-cooled.
[0045] The as-cast microstructure of the prepared Cu-Ni-Si-Ti composite is shown in the attached figure. Figure 1 As shown. Figure 1 Evenly distributed NiTiSi short whiskers and Ni 16 Ti6Si7 particles. According to performance tests, the prepared Cu-Ni-Si-Ti composite material has a hardness of 170.26HV, a tensile strength of 544.4MPa, a conductivity of 45%IACS, and a softening temperature of more than 650℃.
[0046] Example 2
[0047] A particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material is composed of the following raw materials in percentage by mass: 97.73% of electrolytic pure copper, 1.50% of cobalt block, 0.31% of pure silicon wafer and 0.46% of sponge titanium.
[0048] The preparation method of the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material comprises the following steps:
[0049] (1) Electrolytic pure copper is placed at the bottom of the crucible, and the crucible is evacuated in a vacuum medium frequency induction furnace and filled with argon gas for protection before heating. The melting temperature is 1330°C. After the copper is completely melted, cobalt blocks, pure silicon wafers, and sponge titanium are added in sequence. After all are melted, the mixture is kept warm for 5 minutes before vacuum casting. After cooling for 20 minutes, the mixture is released from the furnace and taken out of the furnace.
[0050] (2) Temperature-controlled hot rolling: After removing the surface oxide layer of the Cu-Co-Si-Ti composite ingot, keep it at 1000°C for 4 hours and then hot roll it. The initial rolling temperature is 1000°C, the final rolling temperature is 650°C, and the total hot rolling processing rate is 80%;
[0051] (3) Solution quenching: The hot-rolled Cu-Co-Si-Ti composite material was kept at 1000 °C for 4 h and then water-quenched;
[0052] (4) Cold rolling deformation: the Cu-Co-Si-Ti composite material plate after solid solution treatment is cold rolled, and the total cold rolling processing rate is 60%;
[0053] (5) Aging heat treatment: The Cu-Co-Si-Ti composite cold-rolled sheet was kept at 450°C for 16 h and then air-cooled.
[0054] The as-cast microstructure of the prepared Cu-Co-Si-Ti composite is shown in the attached figure. Figure 2 As shown. Figure 2 A small amount of uniformly distributed NiTiSi short whiskers and Ni 16 Ti6Si7 particles. According to performance tests, the prepared Cu-Co-Si-Ti alloy has a hardness of 158.44HV, a tensile strength of 429.2MPa, a conductivity of 64%IACS, and a softening temperature of more than 540°C.
[0055] Comparative Example 1
[0056] A particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material is composed of the following raw materials in percentage by mass: 95.15% of electrolytic pure copper, 3.20% of nickel block, 0.67% of pure silicon wafer and 0.98% of sponge titanium.
[0057] The preparation method of the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material comprises the following steps:
[0058] First, electrolytic pure copper is placed at the bottom of the crucible, and then vacuumed and filled with argon protection in a vacuum medium-frequency induction furnace and heated at a melting temperature of 1320°C. After the copper is completely melted, nickel blocks, pure silicon wafers, and sponge titanium are added in turn. After all are melted, they are kept warm for 5 minutes and then vacuum cast. After cooling for 20 minutes, the vacuum is released and the furnace is taken out.
[0059] The as-cast microstructure of the prepared Cu-Ni-Si-Ti composite is shown in the attached figure. Figure 3 As shown in the attached figure, the deep corrosion microstructure Figure 4 As shown. Figure 3 and 4 The network-like distribution of NiTiSi whiskers and uniform distribution of Ni 16Ti6Si7 particles. According to performance tests, the prepared Cu-Ni-Si-Ti alloy has a hardness of 94.64HV, a tensile strength of 294.46MPa, a conductivity of 36%IACS, and a softening temperature of more than 650℃.
[0060] Comparative Example 2
[0061] A particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material is composed of the following raw materials in percentage by mass: 91.46% of electrolytic pure copper, 1.60% of cobalt block, 1.60% of nickel block, 0.71% of pure silicon wafer and 4.63% of Cu-40Zr.
[0062] The preparation method of the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material comprises the following steps:
[0063] First, electrolytic pure copper is placed at the bottom of the crucible, and then vacuumed and filled with argon protection in a vacuum medium-frequency induction furnace and heated at a melting temperature of 1340°C. After the copper is completely melted, nickel blocks, cobalt blocks, pure silicon wafers, and Cu-40Zr intermediate alloys are added in turn. After all are melted, they are kept warm for 5 minutes and then vacuum cast. After cooling for 20 minutes, the vacuum is released and the furnace is taken out.
[0064] The as-cast microstructure of the prepared Cu-Co-Ni-Si-Zr composite is shown in the attached figure. Figure 5 As shown. Figure 5 The network-like distribution of (Ni, Co) ZrSi whiskers and the uniform distribution of (Ni, Co) 16 Zr6Si7 particles.
[0065] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material and a preparation method thereof, characterized in that it comprises the following elements in mass percentage: M 1.5-10.0%, Si 0.3-3.0%, X 0.3-2.5%, and the rest is Cu and unavoidable impurities; The M is at least one of Ni and Co; the X is one or more of Ti, Zr, Mn, V, Nb, and Cr.
2. The particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 1, characterized in that: The composite material contains uniformly distributed M 16 X6Si7 particles and MXSi whiskers; The M 16 The volume fraction of X6Si7 particles in the whole alloy is 1.0-8.0%, and the diameter is 1-10 μm; The volume fraction of the MXSi whisker in the whole alloy is 0-4.0%, the radial dimension is 50-300nm, the aspect ratio is 50-300, and the alloy skeleton is formed in a network shape.
3. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 1 or 2, characterized in that: The following steps are involved: (1) Melting: weigh the raw materials according to the ratio, first place the electrolytic pure copper in a crucible, evacuate the vacuum medium frequency induction furnace, fill it with argon protection, and then heat and melt it. After the copper is completely melted, add M metal, crystalline silicon and X metal in sequence. After all are melted, keep the temperature for 5 to 10 minutes and then vacuum cast. After cooling for 20 to 30 minutes, take it out of the furnace to obtain an ingot; (2) Temperature-controlled hot rolling: After removing the oxide layer on the surface of the ingot by turning, the ingot is kept at a temperature of 850-1000°C for 2-6 hours, and then hot rolled to obtain a plate; (3) Solution quenching: The hot-rolled plate is kept at 900-1000°C for 1-4 hours, followed by water quenching; (4) Cold rolling deformation: the plate after solution treatment is cold rolled to obtain a cold rolled plate; (5) Aging heat treatment: The cold-rolled sheet is subjected to aging heat treatment, and then air-cooled to obtain the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material.
4. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: The M metal in step (1) is at least one of a nickel block and a cobalt block.
5. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: In step (1), the X metal is one or more of titanium sponge and Cu-X alloy, and the X is one or more of Zr, Mn, V, Nb and Cr.
6. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: The smelting temperature in step (1) is 1280-1360°C.
7. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: The initial rolling temperature of the hot rolling in step (2) is 850-1000° C., the final rolling temperature is ≥650° C., and the total hot rolling processing rate is 50-95%.
8. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: The total processing rate of the cold rolling in step (4) is 20 to 90%.
9. The method for preparing the particle whisker hybrid reinforced high-strength and high-conductivity copper-based composite material according to claim 3, characterized in that: The temperature of the aging heat treatment in step (5) is 375-525° C., and the insulation time is 0.5-24 h.